Map of the Libyan conflict in the post- Gaddafi period – Analytical study for the period between the National Congress elections until Fajr Libya Operation (2012- 2015) - El- Geroshi, Abdulrauf Rajab (Journal of Economic, Administrative and Legal Sciences, 2022)
After the fall of the Gaddafi regime, the Libyans tried to restructure the state, although they were able to change the regime in months, rebuilding the state was not that easy. One of the most prominent challenges for officials in that period was to address the social division left by the internal war between the February revolutionaries and the Gaddafi regime. In this study, the Libyan conflict in the post- Gaddafi period is analyzed, by presenting an analytical map for the period between the elections of the Transitional National Congress, which is the first legislative council in Libya after the revolution, until Fajr Libya Operation, which is the beginning of the first civil war in the post- Gaddafi era. The study was built according to the qualitative approach, in an attempt to understand and analyze the events based on academic literature and reports. As a result, the study concluded that the Libyan society did not recover from the wounds of the civil war that is experienced, and the absence of transitional justice was one of the direct causes in the emergence of the Libyan conflict because it was not among the priorities of Libyan officials at that stage. In addition to the mentality that prevailed the revolutionaries after their overthrow of the Gaddafi regime, which translated into actions that contributed to an increase in social division.